Methodologies for social life cycle assessment - Jørgensen, Andreas; Le Bocq, Agathe; Nazarkina, Liudmila; Hauschild, Michael (The international journal of life cycle assessment, 2008)
Goal, Scope and Background In recent years several different approaches towards Social Life Cycle Assessment (SLCA) have been developed. The purpose of this review is to compare these approaches in order to highlight methodological differences and general shortcomings. SLCA has several similarities with other social assessment tools, although, in order to limit the expanse of the review, only claims to address social impacts from an LCA-like framework are considered. Main Features The review is to a large extent based on conference proceedings and reports, which are not all easily accessible, since very little has been published on SLCA in the open literature. The review follows the methodological steps of the environmental LCA (ELCA) known from the ISO 14044 standard. Results The review reveals a broad variety in how the approaches address the steps of the ELCA methodology, particularly in the choice and formulation of indicators. The indicators address a wide variety of issues; some approaches focus on impacts created in the very close proximity of the processes included in the product system, whereas others focus on the more remote societal consequences. Only very little focus has been given to the use stage in the product life cycle. Another very important difference among the proposals is their position towards the use of generic data. Several of the proposals argue that social impacts are connected to the conduct of the company leading to the conclusion that each individual company in the product chain has to be assessed, whereas others claim that generic data can give a sufficiently accurate picture of the associated social impacts. Discussion The SLCA approaches show that the perception of social impacts is very variable. An assessment focusing on social impacts created in the close proximity of the processes included in the product system will not necessarily point in the same direction as an assessment that focuses on the more societal consequences. This points toward the need to agree on the most relevant impacts to include in the SLCA in order to include the bulk of the situation. Regarding the use of generic data as a basis for the assessment, this obviously has an advantage over using site specific data in relation to practicality, although many authors behind the SLCA approaches claim that reasonable accuracy can only be gained through the use of site specific data. However, in this context, it is important to remember that the quality of site specific data is very dependent on the auditing approach and, therefore, not necessarily of high accuracy, and that generic data might be designed to take into account the location, sector, size and maybe ownership of a company and thereby in some cases give a reasonable impression of the social impacts that can be expected from the company performing the assessed process. Conclusions This review gives an overview of the present development of SLCA by presenting the existing approaches to SLCA and discussing how they address the methodological aspects in the ISO standardised ELCA framework. The authors found a multitude of different approaches with regard to nearly all steps in the SLCA methodology, thus reflecting that this is a very new and immature field of LCA. Recommendations and Perspectives SLCA is in an early stage of development where consensus building still has a long way. Nevertheless, some agreement regarding which impacts are most relevant to include in the SLCA in order to cover the field sufficiently seems paramount if the SLCA is to gain any weight as a decision support tool. Furthermore, some assessment of the difference between site specific and generic data could give valuable perspectives on whether a reasonable accuracy can be gained from using generic data or whether the use of site specific data is mandatory and, if so, where it is most important.